The Historic Root Cellars in Pierzchnica - Kossakowski, Paweł (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
Paper presents a rather unusual object which is historic root cellars in Pierzchnica. It is a complex of 82 cellars located on the Cellar Hill. The grouping of cellars in one place is unique in the country. The article describes the architecture, design and condition of the cellars. The current inventory of the object made in 2013 is presented, comparing it with the results of the work carried out by the author in 1997. It also presents the concept of adaptation of cellars in terms of opportunities of development in the region.